Sistem Informasi Pengelolaan Sampah Pada Kantor Kelurahan Besusu Timur - Aan Hidayat; Burhanuddin A. Masse; Selvi Agustina (Sekolah Tinggi Manajemen Informatika dan Komputer (STIMIK) Bina Mulia Palu, 2025)
Waste management at the East Besusu Village Office, East Palu District has not met the standards in an orderly manner, where waste data management still uses a manual method, namely written in a ledger or agenda book. Officers must manually record every transaction, such as customer registration, incoming goods and recording savings details. The goal to be achieved in this study is to create a Waste Management Information System at the East Besusu Output Office to help the management process contained in the waste bank to be more effective. The types and sources of data needed in this study are primary data and secondary data. Data collection techniques include observation, interviews and literature. The development of the system uses prototypes. The programming language uses PHP and the database uses MySQL. And the results of the research, namely the Waste Management Information System at the East Besusu Village Office have been completed and can be used to manage waste bank data effectively. The testing process uses the black box method that focuses on the requirements or functional needs of the software being created.